Implementasi Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik (Uu Ite) terhadap Pelaku Judi Online dan Penegakkan Perjudian Online di Kabupaten Garut - Ahya Amalia Deyanti; Neni Ruhaeni (Bandung Conference Series: Law Studies, 2024)
Abstract. This study aims to analyze the implementation and enforcement of criminal law against online gambling perpetrators in Indonesia based on Law Number 19 of 2016 concerning Electronic Information and Transactions. The research method used is normative legal research. Data collected includes regulations related to online gambling, court decisions, and relevant literature. The analysis is conducted by identifying legal provisions governing online gambling, examining the implementation of criminal law enforcement, and evaluating its effectiveness. The research results show that Law Number 19 of 2016 concerning Electronic Information and Transactions has strengthened the legal basis for taking action against online gambling perpetrators, as stipulated in Article 27 Paragraph (2) of the law, which prohibits "Any person who intentionally and without authority distributes and/or transmits and/or makes accessible electronic information and/or electronic documents containing gambling content." However, law enforcement against online gambling still faces several challenges, such as difficulties in identifying perpetrators, tracking financial transactions, and taking enforcement actions in the virtual realm. The conclusion of this study is that criminal law enforcement against online gambling perpetrators based on Law Number 19 of 2016 concerning Electronic Information and Transactions has provided a strong legal basis. Therefore, in enforcing the law against online gambling in Indonesia, it is more appropriate to use Law Number 19 of 2016 concerning Electronic Information and Transactions as the legal basis for criminalizing online gambling actions since in this case, perpetrators who have been proven to commit gambling crimes specifically conduct their illegal activities using internet media. Abstrak. Fenomena judi online semakin berkembang pesat dengan adanya teknologi internet, yang menyebabkan adanya perubahan dalam praktik perjudian dan menimbulkan berbagai tantangan dalam penegakan hukum. Penelitian ini bertujuan untuk menganalisis implementasi dan penegakan hukum pidana terhadap pelaku judi online di Indonesia berdasarkan Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik. Metode penelitian yang digunakan adalah penelitian hukum normatif. Data yang dikumpulkan berupa data sekunder yang terdiri dari, peraturan perundang-undangan yang terkait dengan judi online, putusan pengadilan, dan literatur terkait. Analisis dilakukan dengan mengidentifikasi ketentuan hukum yang mengatur judi online, melihat implementasi hukum dalam penegakan pidana, dan mengevaluasi efektivitasnya. Hasil penelitian menunjukkan bahwa Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik merupakan dasar hukum untuk menindak pelaku judi online, sebagaimana diatur dalam Pasal 27 Ayat (2) dari undang-undang tersebut yang melarang adanya perjudian online. Namun, ketentuan-ketentuan yang telah diatur tersebut belum dapat diimplementasikan pada tataran praktik karena masih menghadapi beberapa tantangan, seperti kesulitan dalam mengidentifikasi pelaku, melacak transaksi keuangan, dan melakukan tindakan penindakan di ranah virtual. yaitu merupakan upaya yang dilakukan melalui usaha yang ditunjukan untuk meningkatkan kesadaran masyarakat seperti, sosialisasi atau penyuluhan”.